Performance of Microhydro Power Plant in Tlocor Village, Banyuwangi, East Java for Households and Post-Harvest Processing - Rahmanto, Dedy Eko; Wibowo, Michael Joko; Faizin, Nur; Fahriannur, Ahmad; Aurelya , Azza Auliya Rahma (Jurnal Agroteknologi, 2025)
Microhydro power plants utilize the kinetic energy of water to spin a turbine and the turbine rotation is used to spin a generator so that it can produce electricity. One example of a microhydro power plant is the Tlocor microhydro located in Tlocor village, Banyuwangi, East Jawa, Indonesia. Tlocor microhydro uses a crossflow turbine and 8 kw synchronous generator. Tlocor microhydro needs to be investigated to determine its performance and development potential. The research was carried out by observing water discharge using a current meter and observing electrical parameters using a power logger and testing voltage drop. The river water discharge is 0.36 m3/s and the turbine used is 0.21 m3/s. The normal daily electrical voltage for Tlocor microhydro is 217.37 volts with a voltage drop at the farthest consumer of 0.68 volts. The resulting electrical frequency is an average of 49.9 Hz. The normal daily electrical power produced by Tlocor microhydro reaches 2605.5 watts. The micro-hydro electrical power produced still has the potential to be increased if the water flow entering the turbine is increased. This can be done if the need for electrical power increases or is used for economic empowerment of communities using Tlocor microhydro.Keywords: electrical, generator, microhydro, water discharge